Pengaruh Loneliness terhadap Problematic Internet Use pada Mahasiswa Dewasa Awal di Perantauan - D, Nurhamidah (Lembaga Yasin AlSys, 2024)
The purpose of this study is to determine the effect of loneliness on problematic internet use in overseas early adult students. Data were collected with the Problematic Internet Use Scale and the Loneliness Scale from 100 samples. Sample selection was used using purposive sampling technique. The data analysis used is simple linear regression analysis. With the results of p value = 0.060 (>0.01), t count = 1.903 (> t table). This shows that there is a negative relationship or there is no influence of loneliness on problematic internet use in early adult students overseas. The coefficient of determination (R2) = 0.036, this shows that loneliness only has a contribution of 3.6% to problematic internet use.